BIOCHEMICAL AND HISTOLOGICAL STUDY OF CYSTICERCUS TENUICOLLIS OF SHEEP IN DUHOK PROVINCE - saad M; Bayati (Basrah Journal of Veterinary Research)
Biochemical composition of Cysticercus tenuicollis (n=11) which isolated from local native sheep showed they have varied averages and ranges in compare with plasma level which reflected various stages of growth .Glucose, cholesterol, triglycerides total protein, uric acid, urea , Ca2+ ,Mg2+ and creatinine levels were involved. Histochemical study of parasite bladder revealed it composed from various kind of cells which are fibroblast , mesenchimal cell ,squamous epithelial like cell , and vacuolated undifferentiated cell with semi-gelatinous mucoid tissue.